Speckle Pattern of the Surface Layer of Titanium Alloy GRADE 2 and Steel 3723HR Samples under Deformation; Materials Science Forum; Vol. 938 : Materials and Technologies in Mechanical Engineering - Ustinov A. M.; Klimenov V. A. Vasily Aleksandrovich; Klopotov A. A.; Abzaev Yu. A.; Ovcharenko V. E. Vladimir Efimovich (2018, 2018)
Title screen